Ketahanan Sistemik Tanaman Kentang Oleh Aplikasi PGPR - Purwantisari, Susiana; Parman, Sarjana; handayani, Dwi; Karnoto, K (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Late blight disease caused by Phytophthora infestans, is probably the single most important disease of potatoes worldwide. Infected plants were quickly killed and were difficult for replanting, causing significant losses for the growers. Various control methods were examined including the use of biocontrol agents of PGPR.Â The research objective was to determine the ability of PGPR product from Ngudi Makmur farmer group local to delay late blight disease incidence on potato plants in the field. The in vivo experiment was carried out at potato land area located at Kledung Â Sub District, Kledung District and Temanggung Regency. Randomized Block Design (RBD) with five treatments was applied with five treatments each of which was placed in a different plot and each plot was filled with 40 plant treatments. On the first plot, no treatment was given (P1); the second plot was given chemical fertilizer (P2), the third plot was supplemented with PGPR one dose (P3), the fourth plot was PGPR two dose (P4), and the last was the fifth plot treated with GA hormone (P5). Result of the research showed that application of PGPR could delay disease intensity until 14 days. These antagonist could be used as biological agents initials to control leaf blight disease. There was an improvement in the quality of potato tubers harvested with the PGPR application compared to controls too.Â